2019
DOI: 10.1126/science.aax3198
|View full text |Cite
|
Sign up to set email alerts
|

A giant exoplanet orbiting a very-low-mass star challenges planet formation models

Abstract: Surveys have shown that super-Earth and Neptune-mass exoplanets are more frequent than gas giants around low-mass stars, as predicted by the core accretion theory of planet formation. We report the discovery of a giant planet around the very-low-mass star GJ 3512, as determined by optical and near-infrared radial-velocity observations. The planet has a minimum mass of 0.46 Jupiter masses, very high for such a small host star, and an eccentric 204-day orbit. Dynamical models show that the high eccentricity is m… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
65
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 105 publications
(74 citation statements)
references
References 71 publications
7
65
0
Order By: Relevance
“…The recent bulk of multi-planetary discoveries around M dwarfs opens a great opportunity to study their orbital architecture in detail. Understanding the dynamics of multi-planet systems around M dwarfs provides an important clue to planet formation around these low-mass stars (Lissauer 2007;Raymond et al 2007;Zhu et al 2012;Anglada-Escudé et al 2013;Coleman et al 2017;Morales et al 2019). Furthermore, the planetary dynamics affect the evolution of any natural satellites; these exomoons can provide critical information on the formation and evolution of a planetary system (see Heller et al 2014), and may 1 See also http://exoplanet.eu even be habitable themselves (Williams et al 1997;Heller & Barnes 2013;Forgan & Dobos 2016).…”
Section: Introductionmentioning
confidence: 99%
“…The recent bulk of multi-planetary discoveries around M dwarfs opens a great opportunity to study their orbital architecture in detail. Understanding the dynamics of multi-planet systems around M dwarfs provides an important clue to planet formation around these low-mass stars (Lissauer 2007;Raymond et al 2007;Zhu et al 2012;Anglada-Escudé et al 2013;Coleman et al 2017;Morales et al 2019). Furthermore, the planetary dynamics affect the evolution of any natural satellites; these exomoons can provide critical information on the formation and evolution of a planetary system (see Heller et al 2014), and may 1 See also http://exoplanet.eu even be habitable themselves (Williams et al 1997;Heller & Barnes 2013;Forgan & Dobos 2016).…”
Section: Introductionmentioning
confidence: 99%
“…The main goal of CARMENES is to discover and characterize Earth-like planets around an initial sample of about 300 M dwarfs (Reiners et al 2018b). To date, the program has already confirmed eight planet candidates from large-scale photometric and spectroscopic surveys (e.g., Trifonov et al 2018;Sarkis et al 2018) and detected more than ten new planets (e.g., Reiners et al 2018a;Kaminski et al 2018;Luque et al 2018Luque et al , 2019Ribas et al 2018;Nagel et al 2019;Perger et al 2019;Zechmeister et al 2019;Morales et al 2019).…”
Section: Introductionmentioning
confidence: 99%
“…EDEN has unique capabilities to target these stars and any planet our survey may detect will serve as a valuable addition to this small sample. The examples of TRAPPIST-1 (Gillon et al 2017) and GJ 3512b (Morales et al 2019) showed how individual discoveries can challenge our current understanding of planet formation and inform tests of competing formation theories. To assess such discoveries in terms of the actual underlying population of exoplanets, it is crucial to be aware of and able to quantify the relevant selection biases.…”
Section: Constraints On Planet Formation Theorymentioning
confidence: 99%